2013
DOI: 10.1016/j.amjcard.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Extracellular Volume by Cardiac Magnetic Resonance Imaging in Patients Treated With Anthracycline-Based Chemotherapy

Abstract: We aimed to determine whether the myocardial extracellular volume (ECV), measured using T1 measurements obtained during cardiac magnetic resonance (CMR) imaging were increased in patients treated with anthracyclines. We performed CMR imaging, an echocardiogram, and measured the ECV in 42 patients with treated with anthracyclines. Data from the CMR study were compared to healthy volunteers. The anthracycline-treated cohort consisted of 21 males and 21 females with a mean age of 55±17 years, presenting a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 25 publications
5
126
1
1
Order By: Relevance
“…17,27 Previous studies show that myocardial ECV quantification correlates with diffuse myocardial fibrosis 17 and is elevated in anthracycline-treated adult subjects. 39,41 Average ECV value in our patient population was similar to previous studies. 27 In agreement with lateral; 6, basal anterolateral; 7, midanterior; 8, midanteroseptal; 9, midinferoseptal; 10, midinferior; 11, midinferolateral; 12, midanterolateral; 13, apical anterior; 14, apical septal; 15, apical inferior; 16, apical lateral; and 17, apex.…”
supporting
confidence: 75%
“…17,27 Previous studies show that myocardial ECV quantification correlates with diffuse myocardial fibrosis 17 and is elevated in anthracycline-treated adult subjects. 39,41 Average ECV value in our patient population was similar to previous studies. 27 In agreement with lateral; 6, basal anterolateral; 7, midanterior; 8, midanteroseptal; 9, midinferoseptal; 10, midinferior; 11, midinferolateral; 12, midanterolateral; 13, apical anterior; 14, apical septal; 15, apical inferior; 16, apical lateral; and 17, apex.…”
supporting
confidence: 75%
“…228,229 One recent study in a small cohort of 13 patients after anthracycline therapy and with normal LV function demonstrated no correlation between anthracycline dose and myocardial fibrosis, though there was a relationship with increased LV volume. 230 Using this technique, Neilan et al 231 recently reported increased extracellular volume as a surrogate of myocardial fibrosis in 42 patients treated with anthracyclines, compared with ageand gender-matched controls. A positive association was found between the extracellular volume and the left atrial volume, and a negative association was found between the extracellular volume and LV diastolic function.…”
Section: Beyond the Lvef: Advanced Cmr Assessmentsmentioning
confidence: 99%
“…49 In a rat model of chronic adriamycin toxicity, rats with histological evidence of chronic cardiotoxicity showed higher native T1 values compared with controls without an increase in myocardial water content or CMR-based T2 values. 40 Similarly, ECV has been recently correlated with anthracycline dose, functional capacity, LV dysfunction, and markers of adverse ventricular remodeling in pediatric 50 and adult 51 patients well after completion of anthracycline-based chemotherapy (Table 5). Preliminary studies (Appendix Table I in the online-only Data Supplement) are also concordant with these findings.…”
Section: Diffuse Myocardial Fibrosismentioning
confidence: 99%